Endocrine disrupting chemicals: A promoter of non-alcoholic fatty liver disease - Chen, Yajie; Wang, Yang; Cui, Ziqiang; Liu, Wenpeng; Liu, Baowang; Zeng, Qiang; Zhao, Xin; Dou, Jian; Cao, Jinglin (Frontiers in Public Health, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disorder. With the improvement in human living standards, the prevalence of NAFLD has been increasing in recent years. Endocrine-disrupting chemicals (EDCs) are a class of exogenous chemicals that simulate the effects of hormones in the body. There has been growing evidence regarding the potential effects of EDCs on liver health, especially in NAFLD. This paper aims to summarize the major EDCs that contribute to the growing burden of NAFLD and to raise public awareness regarding the hazards posed by EDCs with the objective of reducing the incidence of NAFLD.